HUBUNGAN DUKUNGAN KELUARGA DENGAN RISIKO JATUH PADA LANSIA DI DUSUN KAYEN SENDANGSARI PAJANGAN BANTUL - Irvan Saputra; Deby Zulkarnain Rahadian Syah (MEDIA ILMU KESEHATAN, 2020)
Background : Family support is the main for the elderly to maintain the health of the elderly in the face of cognitive and psychosocial physiological changes experienced by the elderly. Low family support will lead to a high risk of falling in the elderly. Objective : This study aims to determine the relationship between family support and the risk of falling in the elderly in Kayen Sendangsari Pajangan Bantul. Method : This study uses a descriptive correlation design with a cross-sectional time approach. Statistical test using Somer's. The sample in this study was 51 elderly people. The sampling technique used was purposive sampling. The measuring instrument used is the family support questionnaire and the TUG test. Result : Based on the research, data regarding high family support were 42 elderly (82.4%), moderate family support was 4 elderly (7.8%), low family support was 5 elderly (9.8%). The risk of falling in the elderly in Kayen Sendangsari Hamlet Pajangan Bantul showed that 32 elderly (62.7%) had a low fall risk and 19 elderly (37.3%) had a moderate fall risk. Somer's test results obtained a p-value of 0.001 <0.05 with a correlation coefficient of -0.481. Conclusion : A negative coefficient value means that the higher the family support, the lower the risk of falling in the elderly. On the other hand, the lower the family support, the higher the risk of falling in the elderly.